Measuring the Link Between Vaccines and Antimicrobial Resistance in Low Resource Settings – Limitations and Opportunities in Direct and Indirect Assessments and Implications for Impact Studies - Holm, Marianne; Zellweger, Raphaël M.; Poudyal, Nimesh; Smith, Katherine HT; Joh, Hea Sun; Marks, Florian (Frontiers in Tropical Diseases, 2022)
The importance of vaccines in combatting antimicrobial resistance (AMR) is commonly accepted. Although scientific reasoning supports the putative connection between vaccines and reduction of AMR, reliably measuring the magnitude and effect of vaccines on antimicrobial resistance is inherently challenging, especially in low resource settings. We review the intrinsic challenges in estimating the effect of vaccines on AMR and discuss the limitations and opportunities in current methods from the host, pathogen, and environment perspectives. We highlight advantages and pitfalls in different epidemiological study designs with a specific focus on impact studies in low resource settings and suggest how these perspectives could be considered in future research.